DIABETIC RETINOPATHY: IMPORTANCE OF PRIMARY CARE PHYSCIAN IN SCREENING - Tamma, Naveen Kumar; Reddy, T Naga; Radha Kishan, N (Journal of Drug Delivery and Therapeutics, 2015)
Objective: The  objective of   this study  is  importance  of  primary care physician in screening  diabetic  retinopahy   patientsMaterial and  Methods  : Patients of  type-2  diabetes mellitus  attending  diabetic clinic in melaka  manipal  medical college , malaysia were  prospectively  reviewed. Risk factors associated   in  study  population were  assessed  by  biochemical parameters, clinical examination  , retinal photographs  and  referred  to  ophthalmology  clinic.Results: The  prevalence of  non  proliferative and  proliferative diabetic retinopathy  with  type-2 diabetic  patients  was 17%  and 1%   with  history of decreased  in vision  above age group of  50 years  . In addition  the  risk  factors  in the  study group  associated with  the  development  of diabetic retinopathy  are   uncontrolled  HbA1c  levels (  27%) , high BMI  (38%  ),  increased total cholesterol (9% )  , uncontrolled fasting blood sugar levels (47%),   and  increased  duration of diabetes.Conclusion: Diabetic  retinopahy  is highly prevalent in patients with type-2 diabetes mellitus. Our findings  indicates  primary care physicians  are   well educated  in regards to diabetic eye disease  and  in identification  of  risk factors due  to  number of  years experience.Keywords:  Proliferative and non proliferative diabetic retinopathy, risk factors, visual disability, type -2 diabetes mellitus